2017
DOI: 10.3390/w9090697
|View full text |Cite
|
Sign up to set email alerts
|

Combined Coagulation and Ultrafiltration Process to Counteract Increasing NOM in Brown Surface Water

Abstract: Membrane hybrid processes-coagulation coupled with ultrafiltration (UF)-have become a common method to comply with the legal, chemical, and microbiological requirements for drinking water. The main advantages of integrating coagulation with membrane filtration are the enhanced removal of natural organic matter (NOM) and reduced membrane fouling. With in-line coagulation, coagulants are patched into the feed stream directly prior to the membrane process, without removing the coagulated solids. Compared with con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 29 publications
1
21
0
Order By: Relevance
“…Historically, Kvarnagården DWTP in Varberg, Sweden had limited treatment of surface water and very high cell concentrations (7 × 10 5 cells/mL) of bacteria in the DWDS. In November 2016, the DWTP was upgraded to ultrafiltration (UF) membranes, combined with flocculation, reducing the input of bacterial cells into the DWDS and removing about 50% of natural, especially high molecular weight, organic carbon [2,21]. This upgrade was closely monitored with FCM and showed that bacterial concentrations in treated and distributed water were substantially lowered by the change in treatment processes [2].…”
Section: Introductionmentioning
confidence: 99%
“…Historically, Kvarnagården DWTP in Varberg, Sweden had limited treatment of surface water and very high cell concentrations (7 × 10 5 cells/mL) of bacteria in the DWDS. In November 2016, the DWTP was upgraded to ultrafiltration (UF) membranes, combined with flocculation, reducing the input of bacterial cells into the DWDS and removing about 50% of natural, especially high molecular weight, organic carbon [2,21]. This upgrade was closely monitored with FCM and showed that bacterial concentrations in treated and distributed water were substantially lowered by the change in treatment processes [2].…”
Section: Introductionmentioning
confidence: 99%
“…This process is aimed at reducing the concentration of suspended solids (SS) and non-settling colloidal particles, thus lowering turbidity and improving water quality [6]. The effectiveness of this process is known to be dependent on the nature of the particles, the type and dosage of the coagulant and the pH of the water [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Treatment consisted of pH adjustment, rapid sand filtration, storage tank 1 with addition of monochloramine, followed by storage tank 2 and 3 and UV disinfection (for more details see ref. 20). In November 2016, UF was added, hereafter defined as UF start, resulting in a treatment chain of rapid sand filtration, storage tank 1, coagulation and UF, pH adjustment, storage tank 2 with addition of monochloramine, storage tank 3 and UV disinfection (Fig.…”
Section: Study Site and Samplingmentioning
confidence: 99%
“…18 Bacteria in chloraminated drinking water included a community with diverse approaches to nitrogen metabolism dominated by Nitrosomonas (AOB), and Nitrospira (NOB) and accompanied by heterotrophs such as Sphingomonas 19 and these taxa were recently identified as actively conducting nitrification in diverse pipe biofilms. 13 When a drinking water treatment plant (DWTP) in Varberg, Sweden, installed an ultrafiltration (UF) facility with two-stage filtration and in-line coagulation at the primary membrane stage, 20 the new finished water (FW) contained virtually no bacteria, and less and different natural organic matter (NOM). 11 The impact of this change on the bacterial community was examined by collecting water, swabbing the surface of the biofilm, and scraping to remove deep biofilm from multiple sections of pipe in series and excavated from the operational DWDS.…”
Section: Introductionmentioning
confidence: 99%